2018
DOI: 10.1038/s41598-018-31575-3
|View full text |Cite
|
Sign up to set email alerts
|

Triple Fluorescence staining to Evaluate Mechanism-based Apoptosis following Chemotherapeutic and Targeted Anti-cancer Drugs in Live Tumor Cells

Abstract: We present a protocol for live cancer cell-imaging by triple-fluorescent staining to test 3 crucial mechanisms of apoptosis; the enzymatic activity of executioner caspase3, caspase-dependent phosphatidylserine presentation on the cell surface and mitochondrial function. We standardized a protocol to co-stain live tumor cells with the NucView488-Casp3 substrate, CF594 AnnexinV, and MitoViewBlue. We validated this protocol following apoptosis induction with paclitaxel or in combination with BKM120. Fluorescent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…Previous works have illustrated that the advancement of apoptosis in tumor cells by flavaglines is the essential mechanism underlying the inhibition of tumor cell growth. [28,29] Similarly, in the current work, A2074 contributed to cell-cycle arrest in K562 cells through apoptosis. Hoechst staining visualized apoptotic nuclei with condensed chromatins.…”
Section: Apoptotic Effect Of A2074 In K562 Cellssupporting
confidence: 60%
“…Previous works have illustrated that the advancement of apoptosis in tumor cells by flavaglines is the essential mechanism underlying the inhibition of tumor cell growth. [28,29] Similarly, in the current work, A2074 contributed to cell-cycle arrest in K562 cells through apoptosis. Hoechst staining visualized apoptotic nuclei with condensed chromatins.…”
Section: Apoptotic Effect Of A2074 In K562 Cellssupporting
confidence: 60%
“…( E ), mean ± SE of ΔΨ m in the absence (Ctrl) and presence of NaHS (100 µM, 72 h). ΔΨ m was measured by evaluating tetramethylrhodamine, methyl ester (TMRM) fluorescence [ 67 ].…”
Section: Figurementioning
confidence: 99%
“…Using the microscopy method, cells labeled with DAPI has been shown to identify apoptosis based on nuclear morphology. [ 63,64 ] As represented in Figure 4 and Figure 5A–C our results showed that the palmitic acid treatments (50–150 μM) for 24 and 48 h enhance the apoptosis in the L6 myoblasts. Similar studies were conducted in the human vascular endothelial cells, showing apoptosis triggered by the saturated fatty acid.…”
Section: Discussionmentioning
confidence: 59%